Strategi Penghapusan Sarana dan Prasarana Pendidikan - Fitria Handayani; Rayyifa Zahra Marella; Damar Ary Yahya; Zahrotul Munawwaroh (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
The management of educational facilities and infrastructure is not only related to procurement and maintenance but also includes the disposal process as an important part of educational asset management. However, in practice, the disposal of facilities and infrastructure in Indonesian educational institutions still faces various problems, such as complex administrative procedures, limited human resources, and budget constraints. This article aims to identify and analyze effective strategies for the disposal of educational facilities and infrastructure based on current literature reviews. This research uses a systematic literature review method by examining scientific journals and academic books published in 2020–2026. Data were analyzed using thematic content analysis techniques to identify concepts, strategies, obstacles, and managerial implications of the disposal of educational facilities and infrastructure. The results of the study indicate that effective disposal strategies rely on inventory-based planning and needs prioritization, administrative procedures integrated with regulations, as well as control and supervision through continuous audits and evaluations. These findings are expected to serve as a practical reference for school and madrasah managers in improving the effectiveness of educational facilities and infrastructure management.